Organ preservation in rectal cancer with contact x-ray brachytherapy (Papillon): a refined Swiss protocol to improve real-world feasibility - Picardi, Cristina; Caparrotti, Francesca; Brunner-Schaub, Nora; Christen, Daniel; Fargier-Voiron, Marie; Drepper, Michael; Von Laufen, Alain; Montemurro, Michael; Ris, Frederic; Matzinger, Oscar (Frontiers in Oncology, 2025)
Rectal cancer is an increasingly prevalent malignancy, with growing interest in organ preservation strategies as an alternative to radical surgery, particularly for tumors of the mid-lower rectum. Radiotherapy plays a central role in these approaches and contact X-ray brachytherapy (CXB or Papillon technique) allows for safe dose escalation directly to the tumor, enhancing local control while minimizing toxicity. This report describes the development and implementation of a refined protocol for Papillon CXB, addressing technical challenges related to patient comfort, applicator placement, and procedural accuracy. By the end of 2024, a total of 129 patients with mid-lower rectal cancer had been treated with Papillon CXB in Swiss centers. In February 2022, a refined protocol was introduced, incorporating procedural sedation (Propofol), the lateral decubitus position, and close collaboration with gastroenterologists to improve tumor visualization and precise applicator placement. This updated approach has been applied to 73 patients, mainly with curative intent and organ preservation goals. Sedation significantly improved patient comfort and reduced movement during applicator insertion. The applicator demonstrated excellent stability, even in anatomically challenging cases. The procedure proved to be straightforward, smoothly integrated into clinical workflows, and well-tolerated by patients, with high satisfaction reported by both patients and the medical team. This Swiss protocol offers a practical and patient-centered refinement of Papillon CXB. By addressing critical technical and clinical challenges, it enhances procedural feasibility and safety, ultimately supporting optimal oncological outcomes and wider adoption in rectal cancer management.